2017
DOI: 10.1007/s12217-017-9543-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronoamperometric Study of Ammonia Oxidation in a Direct Ammonia Alkaline Fuel Cell under the Influence of Microgravity

Abstract: This is a study of the chronoamperometry performance of the electrochemical oxidation of ammonia in an alkaline fuel cell for space applications. Under microgravity the performance of a fuel cell is diminished by the absence of buoyancy since nitrogen gas is produced. The following catalysts were studied: platinum nanocubes of ca. 10nm, platinum nanocubes on a Vulcan carbon support and platinum on carbon nanoonion support of ca. 10nm. These nanomaterials were studied in order to search for catalysts that may r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Then, the development of electrochemical sensors and selective catalysts for the degradation of ammonia to a harmless molecule such as the N2 gas, are a subject of intense research in electrochemistry [75]. Other interest on the ammonia electro-oxidation is because, from the electrochemical energy conversion point of view, ammonia is a potential candidate to be used as fuel in direct "ammonia" fuel cells [76,77]. In extreme alkaline media, the standard potential for the ammonia oxidation reaction NH3 (g) + 3OH -(aq) ⇄ ½N2 (g) + 3H2O (l) + 3eis E 0 ≃ -0.770 VSHE (or ~0.055 VRHE) [76].…”
Section: Electro-oxidation Of Ammoniamentioning
confidence: 99%
“…Then, the development of electrochemical sensors and selective catalysts for the degradation of ammonia to a harmless molecule such as the N2 gas, are a subject of intense research in electrochemistry [75]. Other interest on the ammonia electro-oxidation is because, from the electrochemical energy conversion point of view, ammonia is a potential candidate to be used as fuel in direct "ammonia" fuel cells [76,77]. In extreme alkaline media, the standard potential for the ammonia oxidation reaction NH3 (g) + 3OH -(aq) ⇄ ½N2 (g) + 3H2O (l) + 3eis E 0 ≃ -0.770 VSHE (or ~0.055 VRHE) [76].…”
Section: Electro-oxidation Of Ammoniamentioning
confidence: 99%
“…Pt has been studied mostly since it yields the highest AOR peak current and Ir is known for its lowest onset potential. [11][12][13][14][15]16 Thus, Pt, Ir, and PtIr alloy nanocatalysts are the baseline materials for AOR studies. 17,18 Quantitative comparison of AOR catalysts remains elusive because the data accumulated so far were obtained using various potential sweep rates, ammonia concentrations, pH values, and were not normalized to PGM loadings.…”
mentioning
confidence: 99%
“…Nicolau et al 29 reported that the oxidation of ammonia with different Pt-based nanocatalysts resulted in a decreased performance of 20-65% in microgravity environments in comparison to terrestrial control experiments. Similarly, Acevedo et al 31 showed that the performance of ammonia-based alkaline fuel cells decreased in microgravity environment. Nicolau et al (2012) attributed the current decrease to the lack of buoyancy-driven mixing in the near-absence of gravitation (Fig.…”
Section: Fuel Cellsmentioning
confidence: 92%
“…Besides hydrogen and methanol, fuel cells have been proposed utilizing ammonia as a fuel [29][30][31] . Ammonia has recently been considered as the main substitution for hydrogen and the next generation fuel 32 due to its high energy density (12.6 MJ L −1 ) and the easiness of storage and transportation 29 .…”
Section: Fuel Cellsmentioning
confidence: 99%